Applicability of the field deformation measurement data in predicting the stability of embankment slopes - Nawarathna, T.H.K.; de Silva, L.I.N. (Sri Lankan Geotechnical Society, 2015)
Matsuo chart, which is based on the field measurement of the settlement at the center of an embankment and the lateral deformation at the toe, is widely used in practice in evaluating the stability of embankments. However, the applicability and the accuracy of the Matsuo chart in evaluating the stability of embankment slopes under varying geometrical and subsoil conditions needs further investigations. Therefore, the current study aimed at investigating the above using the finite element method and limit equilibrium approach. Stability of different embankments including several case histories were analyzed by varying the embankment height, width and the sub soil parameters and factor of safety values were determined by the use of Matsuo chart, finite element method and the limit equilibrium method. Results of the current study suggest that Matsuo chart can reasonably predict the stability of embankment slopes under varying embankment conditions.
Keywords: Matsuo chart; Finite element analysis; Limit equilibrium method